A novel analytical method for the determination of cadmium in sorrel and rocket plants at ultratrace levels: Magnetic chitosan hydrogels based solid phase microextraction-slotted quartz tube-flame atomic absorption spectrophotometry - Er, Elif Ozturk; Maltepe, Esra; Bakirdere, Sezgin (ELSEVIER, 2018)
A novel preconcentration method based on the magnetic chitosan hydrogels (MCH) was developed for trace level determination of cadmium in sorrel (Rumex acetosella) and rocket (Eruca saliva) as edible plants. Magnetic Fe3O4@chitosan composites were synthesized, characterized and used to obtain lower detection limits for cadmium by slotted quartz tube (SQT) - atomic absorption spectrophotometry (FAAS). The Box Behnken multivariate design was used to optimize the experimental variables. Under the optimum conditions, developed method provided 97.5 fold enhancements in detection power when compared to conventional FAAS. Proposed method also provided low detection and quantification limits (0.20 and 0.68 ng/mL, respectively), high precision with %RSD of 5.3 and high accuracy with recoveries ranged from 96.0-110.4% for Rumex acetosella and Eruca saliva matrices, respectively. The results demonstrated that magnetic chitosan hydrogels could be promising materials to be used as sorbent material in solid phase microextraction yielding simple, cost-effective and environmentally friendly preconcentration process.
Keywords: Cadmium; Magnetic chitosan hydrogels; Eruca saliva; Rumex acetosella; SQT; OPTICAL-EMISSION-SPECTROMETRY; MULTIWALLED CARBON NANOTUBES; CLOUD POINT EXTRACTION; HEAVY-METAL IONS; PRECONCENTRATION PHASE; BIOLOGICAL SAMPLES; FOOD SAMPLES; WATER; LEAD; NANOPARTICLES; Chemistry